An application of activity theory to the "problem of e-books". Issue 9 (September 2020) - Kirby, Karen; Anwar, Muhammad N.
Abstract: The "problem of e-books" is defined as the difficulty improving the adoption rates of e-books by students. The adoption rates of e-books for academic use remain low, and research into the reasons for this have resulted in inconclusive findings. Factors such as student perception, and variations in experimental methodology and technology, contribute to difficulties in generalising findings and establishing conclusive causes for this problem. To better understand the causal factors for low adoption rates and the student's experience with ereaders and digital text, an investigation was conducted by the lead researcher as a student enrolled in a postgraduate course. The experiment was designed using e-book and digital text documents on an ereader for academic study and the results analysed with the framework of Activity Theory. This methodology allowed exploration of the problem within the authentic experience of a student to examine the effects of this social environment on ereader and e-book use. Analysis of the work domain was conducted and a comparative assessment of the observed effect of using the digital documents on an ereader compared with the paper book. Findings show that attempts to apply self-regulation and metacognitive learning techniques within the activity using the ereader were abandoned due to breakdowns in operations, and that this resulted in a perceived lower quality of achievement. The effect on the processes used by the student were extreme and were observed to be highly dependent on the student's use of specific learning strategies. The experimental methodology employed in this investigation enabled identification of the role of the social environment in the use of course documents on an ereader for academic study. The functionality of the ereader was such an extremely poor fit with the observed academic processes that a redesign approach for ereader and e-book technology is proposed as a solution to the low adoption rates of e-books. Abstract : Education; Information science; Activity theory; E-books; E-readers; Academic learning; Metacognition; Autoethnography; Reading